Academic Migration, Discipline Knowledge and Pedagogical Practice
XXV, 218 p. 12 illus.
Keywords: This volume makes a distinctive and innovative contribution to the globalisation of higher education literature by highlighting the myriad benefits of academic migration. Sixteen academic migrants across the Asia-Pacific region reflect on their experiences and wisdom gained across geographical, cultural and disciplinary domains. Each one provides an authentic account of ways in which their experiences and insights have benefited their host institutions and enhanced their pedagogical practice. The groundbreaking volume calls for a shift in academic culture – one in which academic migrants are respected for their cultural, social and intellectual resources, their enhanced interpretive ability and their capacity to view the world through multiple lenses. Are these not the characteristics of educators which universities seek in their efforts to internationalise their institutions and develop in their students an understanding of global citizenship? The volume forges new territory in articulating the relationship between academic migrants, conceptual understanding and the construction of knowledge. The following themes are addressed in this book: Migration of Ideas, Conceptual Understanding and Pedagogical Enrichment Indigenous Pedagogies and Bridging Worldviews Changing Academic Identities and Reshaping Pedagogies Teaching Practice and the Academic Diaspora.